Biomass equations for rockrose (Cistus laurifolius L.) shrublands in North-central Spain - Bados, Raquel; Esteban, Luis Saúl; Esteban, Jessica; Fernández-Landa, Alfredo; Sánchez, Tomás; Tolosana, Eduardo (Forest Systems, 2021)
Aims of the study: To construct biomass weight equations for rockrose (Cistus laurifolius L.) shrublands in North-central Spain comparing different methodologies and evaluating the applicability of the current Spanish open PNOA-LiDAR data.Area of study: The growing extension of Mediterranean shrublands associated with a high wildfire risk in a climate change scenario is considered a relevant source of biomass for energy use and bioproducts. Quantifying the biomass load of the shrublands provides essential information for adequate management, calling for the development of equations to estimate said biomass loads in the most extensive monospecific shrublands.Materials and methods: Biomass dry weight from 290 destructive sampling plots (ø4m) and 426 individual plants along with LiDAR data from PNOA were related to dasometric parameters to fit weight per surface and weight per plant equations.Main results: Three new equations improve rockrose biomass estimations in North-central Spain: a) Weight per unit area (tDM.ha-1) equation (Eq. 1) based on apparent biovolume (product of crown cover in percentage by average height in meters) (Radj2 0.69, MAE 26.1%, RMSE 38.4%); b) Weight per plant (kgDM.plant-1) equation (Eq. 2) from height and crown diameter (Radj2 0.87, MAE 26.5%, RMSE 45.2%) and c) Weight per unit area equation (tDM.ha-1) (Eq. 3) based on LiDAR data contrasted with field data (Radj2 0.89, MAE 15.1%, RMSE 22.9%).Research highlights: Eq. 1 and Eq. 3 combined with high resolution LiDAR information offer rockrose (Cistus laurifolius L.) biomass estimations without added field work costs that are an improvement on certain more general studies carried out in other areas of Spain.Keywords: Shrub; wildfire prevention; forest energy; LiDAR; weight biomass equations.